2021
DOI: 10.1063/5.0033689
|View full text |Cite
|
Sign up to set email alerts
|

The translocation dynamics of the polymer through a conical pore: Non-stuck, weak-stuck, and strong-stuck modes

Abstract: The external voltage-driven polymer translocation through a conical pore (with a large opening at the entry and a small tip at the exit) is studied by using the Langevin dynamics simulation in this paper. The entire translocation process is divided into an approaching stage and a threading stage. First, the approaching stage starts from the polymer entering the large opening and ends up at a terminal monomer reaching the pore tip. In this stage, the polymer will undergo the conformation adjustment to fit the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 67 publications
3
12
0
Order By: Relevance
“…As the apex angle (see Fig. 1 a) is varied, the translocation time shows non-monotonic features, consistent with earlier reports 41 , 60 63 . We comment on the detailed behavior of the waiting time distribution with varying force strengths and .…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…As the apex angle (see Fig. 1 a) is varied, the translocation time shows non-monotonic features, consistent with earlier reports 41 , 60 63 . We comment on the detailed behavior of the waiting time distribution with varying force strengths and .…”
Section: Introductionsupporting
confidence: 90%
“…Further, the passage time is a non-monotonic function of the apex angle of the cone for a given length of the channel. Langevin dynamics studies of flexible polymer translocation through conical channels have shown that translocation is dependent on channel structure and interactions of the polymer with the channel 41 , 62 , 63 . Most biopolymers and proteins are however semiflexible with an energy cost associated in bending, characterized by the bending rigidity of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Having a high voltage applied across the pore might result in false translocation events. Furthermore, as mentioned earlier, a cone-like shape only allows a few nucleotides around the one that is translocating due to the narrow constriction at the end [ 181 , 182 ], which enhances the accuracy of the current measurement.…”
Section: Controlling the Speed Of Translocationmentioning
confidence: 99%
“…If a sequence remains engaged in the channel for a long time, we consider it to be trapped [37] and it has to escape through energy barriers opposing both translocation and rejection. The distribution of sojourn times under a random uncorrelated force (the time distributions discussed here are not self-averaging) is discussed in [32].…”
Section: Theorymentioning
confidence: 99%